Radicular Cyst: A Review Of The Clinical, Radiographic, And Management Features - Dyah Ajeng Ramadhani; Ichda Nabiela Amiria Asykarie (International Journal of Health Engineering and Technology, 2026)
Radicular cyst is the most common inflammatory odontogenic cyst found in the jaws and is generally associated with pulp necrosis due to chronic infection. This lesion often develops asymptomatically and is frequently detected incidentally during radiographic examination. This study aims to review the clinical features, radiographic characteristics, and management of radicular cysts based on a systematic literature review. The method used was a Systematic Literature Review by collecting data from various relevant scientific databases. The results indicate that clinically, radicular cysts are mostly asymptomatic in the early stages, but in advanced conditions, they may cause swelling, pain, and bone expansion. Radiographically, the lesion typically appears as a well-defined radiolucent area at the apex of a non-vital tooth; however, definitive diagnosis still requires histopathological examination. Advanced imaging modalities such as CBCT and MRI improve diagnostic accuracy. The management of radicular cysts depends on the size and characteristics of the lesion. Non-surgical endodontic treatment is the primary approach for small to moderate lesions, while surgical interventions such as enucleation or marsupialization are indicated in more complex cases. In conclusion, a comprehensive approach involving clinical, radiographic, and histopathological evaluation is essential for accurate diagnosis and effective management of radicular cysts.